Substitusi Emulsifier Non-Halal dengan Ekstrak Berbasis Polifenol dan Protein Nabati: Substitution of Non-Halal Emulsifiers with Polyphenol- and Plant Protein-Based Extracts - Nur Hidayat, Robby; Muhamad Nurdiansyah, Adi; Windayani, Neneng; Cahyanto, Tri (Universitas Djuanda, 2026)
Emulsifiers are crucial for ensuring product stability in the food, cosmetics, and pharmaceutical sectors. Many emulsifiers, however, are sourced from non-halal origins, such as lard or other animal products that contravene Islamic law. Moreover, certain synthetic emulsifiers may provoke apprehensions related to health and environmental sustainability. This study aims to determine the most stable oil-in-water (O/W) emulsion formulation utilizing soy protein isolate (SPI) and mangosteen peel extract, evaluated through centrifugation tests, thermal treatments, pH tests, and storage stability, as a potential natural emulsifier to substitute non-halal emulsifiers. This study used a laboratory-based experimental methodology. The findings indicated that the polyphenol extract comprised 18.37% polyphenols, whereas the soy protein isolate had a concentration of 7.056 mg/mL. Four emulsions were formulated with varying concentrations of soy protein isolate: 1.0%, 2.5%, 5.0%, and 10.0%. The study revealed that polyphenols from mangosteen peel and vegetable protein from soybeans exhibit potential as emulsifiers. The optimal formulation for creating an emulsion consisted of 5.0% soy protein isolate, 0.5% mangosteen peel extract, 89% distilled water, and 9.5% sunflower oil. The emulsion with the optimal formulation exhibited excellent stability, as evidenced by its stability parameters concerning temperature, pH, centrifugation, and storage.